UPAYA GURU MENGENALKAN MEMBACA PERMULAAN PADA ANAK USIA 5-6 TAHUN DI TK - Rumantir, Silvia Maya; R, Marmawi; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractReading the beginning for ages 5-6 years is included in the field of basic development, especially the concept of literacy, namely recognizing letter symbols, mention the letters symbols that are known, recognize the sound of the initial letters of the names of objects around it, mention groups of images that have the same initial sound / letter, understand the relationship between sound and letter form, read their own names and write their own names. The purpose of this study was to describe the efforts of teachers in introducing early reading to children aged 5-6 years at TK Kanaan Kubu Raya. With the number of teacher subject observations totaling 4 people. The efforts of teachers in introducing initial reading to students which have been applied using the spell method show very significant results. In introducing early reading to children, the teacher then combines letters into syllables using the method the child institution is able to combine letters into open words quite well. Children love the initial reading activity with the spelling method through singing activities, they have had enough good development. Strengthening is very important given in the initial reading process so that the development of the child's ability to develop optimally as a provision to proceed to the next stage.Keywords: Reading Beginnings, Spelling Methods, Institutional Word Methods